Prevalence and Associated Risk Factors of Giardia Infection among Indigenous Communities in Rural Malaysia - Choy, S.H.; Al-Mekhlafi, H.M.; Mahdy, M.A.K.; Nasr, N.N.; Sulaiman, M.; Lim, Y.A.L.; Surin, J. (Nature Publishing Group, 2014)
This study was carried out to investigate the prevalence and risk factors of Giardia infection among indigenous people in rural Malaysia. Faecal samples were collected from 1,330 participants from seven states of Malaysia and examined by wet mount and formalin-ether sedimentation methods while demographic, socioeconomic and environmental information was collected using a pre-tested questionnaire. The overall prevalence of Giardia infection was 11.6% and was significantly higher among those aged ≤ 12 years compared to their older counterparts. Multivariate logistic regression identified age of ≤12 years, lacking of toilet at household, not washing hands before eating, not washing hands after playing with animals, not boiling water before consumption, bathing in the river, and not wearing shoes when outside as the significant risk factors of Giardia infection among these communities. Based on a multilocus genotyping approach (including tpi, gdh and bg gene sequences), 69 isolates were identified as assemblage A, and 69 as assemblage B. No association between the assemblages and presence of symptoms was found. Providing proper sanitation, as well as provision of clean drinking water and proper health education regarding good personal hygiene practices will help significantly in reducing the prevalence and burden of Giardia infection in these communities.